Cytomegalovirus reactivation is frequent in multiple myeloma patients treated with daratumumab‐based regimens - Danilo De Novellis; Raffaele Fontana; Bianca Serio; Emilia Vaccaro; Roberto Guariglia; Denise Morini; Michela Rizzo; Valentina Giudice; Carmine Selleri (Cancer Medicine, 2024)
Abstract Background Viral reactivations are frequent in hematologial patients due to their cancer‐related and drug‐induced immunosuppressive status. Daratumumab, an anti‐CD38 monoclonal antibody, is used for multiple myeloma (MM) treatment, and causes immunosuppression by targeting CD38‐expressing normal lymphocytes. In this single‐center two‐arm real‐life experience, we evaluated incidence of cytomegalovirus (CMV) reactivation in MM patients treated with daratumumab‐based regimens as first‐ or second‐line therapy. Methods A total of 101 consecutive MM patients were included in this study and were divided into two cohorts: daratumumab and nondaratumumab‐based (control) regimens. Patients treated with >2 lines of therapies were excluded to reduce the confounding factor of multi‐treated cases. Primary endpoint was the CMV reactivation rate. Results CMV reactivation rate was significantly higher in the daratumumab cohort compared to control group (33% vs. 4%; p < 0.001), also with higher CMV‐DNA levels (>1000 UI/mL in 12% of cases; p < 0.05). However, only one subject developed a CMV disease with severe pneumonia, while 12% of patients were successfully treated with preemptive therapy with valganciclovir. No subjects in the control cohort required anti‐CMV agents (p = 0.02). Conclusion Our single‐center retrospective experience showed that daratumumab might significantly increase the risk of CMV reactivation in MM, while currently underestimated and related to morbility and mortality in MM patients under treatments. However, further validation on larger and prospective clinical trials are required.